2017
DOI: 10.1016/j.jpsychires.2016.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Specific expectancies are associated with symptomatic outcomes and side effect burden in a trial of chamomile extract for generalized anxiety disorder

Abstract: Objective Patient expectancies are hypothesized to contribute to the efficacy and side effects of psychiatric treatments, but little research has investigated this hypothesis in the context of psychopharmacological therapies for anxiety. We prospectively investigated whether expectancies predicted efficacy and adverse events in oral therapy for Generalized Anxiety Disorder (GAD), controlling for confounding patient characteristics correlating with outcomes. Methods Expectancies regarding treatment efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 60 publications
1
9
0
1
Order By: Relevance
“…Other studies have found that expectations of treatment effectiveness are important, [43][44][45][46] but there are two arguments against the role of expectations in our results. First, Study 1 participants did not know if they were getting true or sham acupuncture, but Study 3 participants knew that they were getting true acupuncture.…”
Section: Discussionmentioning
confidence: 56%
“…Other studies have found that expectations of treatment effectiveness are important, [43][44][45][46] but there are two arguments against the role of expectations in our results. First, Study 1 participants did not know if they were getting true or sham acupuncture, but Study 3 participants knew that they were getting true acupuncture.…”
Section: Discussionmentioning
confidence: 56%
“…The instrument is a 4-question subject-report questionnaire rated on a scale of 1–5 (wherein 1 is total disagreement with a statement and 5 is total agreement), which assesses a subject’s expectation that treatment will relieve his/her primary anxiety symptoms and increase his/her coping abilities and vitality (Keefe et al, 2017). Sample items include a subject’s relative agreement with the statements that with chamomile treatment “I will be able to cope with my anxiety better” and that “The symptoms of my anxiety will disappear.” The METE had good internal consistency in our sample (Cronbach’s alpha = 0.88), and has been found to predict symptom relief during treatment (Keefe et al, 2017). Subjects completed the METE at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…If baseline GAD-7 were not included in the model, any obtained relationships between changes in cortisol and symptomatic improvements could easily be due to regression to the mean simultaneously occurring for both variables. In addition, subject pretreatment expectancies for treatment improvement were entered as a clarifying covariate of the relationship between symptom change and cortisol change to control for this component of the placebo effect, as expectancies predict symptom change in this trial (Keefe et al, 2017). 1 The predicted variable in the mixed model was a given salivary cortisol measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Such effects are potentially relevant in clinical practice because they might lead to better patient health and more effective therapy outcomes. In fact, several studies have shown a positive association between optimistic outcome expectations of patients and favorable therapeutic improvements for a variety of conditions and symptoms, such as disability after surgical interventions (19), hypertension (20, 21), depression (22), anxiety (23, 24), other psychiatric disorders (25), and pain (26).…”
Section: Introductionmentioning
confidence: 99%